Spiritual Care at the Time of Pendemic An Analytical Study of Early Muslim Scholars Views & Practice: أهمية العناية الروحية في تسلية المصاب في حالة الوباء قراءة تحليلية في تصورات العلماء المسلمين الأوائل وخبرتهم - Machouche, Salah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This study aims to investigate early Muslim scholars' understanding of the pandemic, as well as their efforts to dealing with, reducing, and curbing its psychological repercussions. The study employs an inductive and analytical interpretation of early Muslim texts on pandemics. The study shows that early Muslim thinkers interpret the pandemic from various perspectives including the divine decree, nature of human behaviour and his connection with God, and the natural world’s circumstances. الإسلام يسعى هذا البحث إلى دراسة واستجلاء رؤية العلماء المسلمين الأوائل في ظاهرة الوباء وطرق مواجهتها واحتواء آثارها النفسية والاجتماعية، اعتمد البحث على قراءة استقرائية تحليلية لمؤلفات العلماء المتقدمين في تفسير ظاهرة الوباء وتصميمهم الحلول والإجراءات الوقائية لمواجهته. ولقد خلص البحث إلا أن رؤية المتقدمين للوباء كانت متنوعة وشاملة اتخذت بعير الاعتبار ثلاث زوايا أساسية وهي: الأمر الإلهي، ونوعية السلوك الإنساني وارتباطه بالله وحال البيئة الطبيعية. وبينت أن سلوك الإنسان الظاهر والباطن وعلاقته بالله ونشاطه كلها محددات أساسية في نشوء الكوارث والأوبئة فلابد من إدخالها في تدبير الحلول لمواجه الوباء.